Construction of micro scale coral propagation media controller system with Arduino Nano and Flutter SDK - Utomo, Aulia Desy Nur; Abimanyu, Abimanyu; Prihantoro, Cahyo (Institute of Computer Science (IOCS), 2025)
Rising sea temperatures due to global warming and human activities in Indonesia threaten coral reef sustainability, leading to bleaching and mass mortality. In 2016, 50% of coral colonies in Gili Matra experienced bleaching, 11% were pale, and 1% faced mortality. To mitigate damage, controlled coral cultivation in isolated media offers an alternative to open-ocean methods, allowing precise water quality management. Coral transplantation, involving fragmentation and placement in controlled environments, enhances rehabilitation efforts. An IoT-based controller enables real-time monitoring and automation of life-support systems, including supplementation pumps, photosynthetic lamps, top-up pumps, cooling fans, and current pumps. System performance shows consistent lamp scheduling, supplementation dosage with a deviation of ±1-2%, precise top-up activation, current pump scheduling with a 1s deviation, and optimal water parameters (alkalinity 8.3 dKH, calcium 420 ppm, magnesium 1050 ppm, salinity 1.025).